PEDESTRIAN BEHAVIOUR AT A SIGNALISED INTERSECTION IN BANDUNG - ( NIM : 269 95 0170), Subarjo
SUMMARY: This research is focused by pedestrian violations the green man, utilisation the push button and pedestrian crossing outside the marking and pedestrian waiting time. Pedestrian flow maximum occurred begin to start green man (0-5 sec) is 56.5 percent (8955 pedestrian per hour of green). The maximum violations the green man occurred during flashing green man and all-red is 0-15 sec, viz. 82 percent. The average numbers of the pedestrian violation the green man during observation were 196.5 pedestrian per hour. However, the number of pedestrian waiting time reciprocal to waiting time function, the largest frequency occurred at the waiting time 0-5 sec namely 14.9 percent and the smallest waiting time at greater than 70 sec. The mean number of pedestrians waiting time was 0.9 pedestrian. It can be represented by the negative exponential distribution. The utilisation of the push button is not effective because pedestrians only pushed the button during 3 percent of the observed signal cycles. Furthermore this does not appear to be any significant difference between the green man time as a percentage of the cycle time for pedestrians pushing or not pushing the button. The available crosswalk is often utilised by pedestrian crossing. Pedestrians at around pedestrian bridge that crossing is objection to crosswalk facility. Since they must be turned. Therefore they are directly to crossing at random point. The number of pedestrians crossing outside the marking was influenced by gap of vehicle flow. There was some relationship both of them although the correlation was not so good. The most suitable model was a logarithmic model. Not correlation or influence between vehicle flow and average waiting time could be found. That may be because the longer pedestrian waiting time tend to encourage violations; the highest pedestrian violations occurred at the start of DONT WALK. While pedestrian flow was influenced by total pedestrian waiting time and represented by the geometric model. When the pedestrians waiting time increases, the number of pedestrians crossing in the marking also increases. The most pedestrians crossing is still at crosswalk, because 77 percent pedestrian flow is at crosswalk, although there are relationship between pedestrian flow and pedestrian crossing at around crosswalk.